2012
DOI: 10.1002/pro.2153
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of a tethered Lmo2LIM2/Ldb1LID complex

Abstract: LIM-only protein 2, Lmo2, is a regulatory protein that is essential for hematopoietic development and inappropriate overexpression of Lmo2 in T-cells contributes to T-cell leukemia. It exerts its functions by mediating protein-protein interactions and nucleating multicomponent transcriptional complexes. Lmo2 interacts with LIM domain binding protein 1 (Ldb1) through the tandem LIM domains of Lmo2 and the LIM interaction domain (LID) of Ldb1. Here, we present the solution structure of the LIM2 domain of Lmo2 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We visualized I322 within available structures of an LMO2-LID fusion protein (PDB accession number 2XJZ) (Fig. 3B) (53)(54)(55) and found that it was in close proximity to LMO2 residues L64 and L71, suggesting a potential hydrophobic interface. L64 and L71 were both highly conserved in LMO2 paralogs, supporting an important functional role for these residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We visualized I322 within available structures of an LMO2-LID fusion protein (PDB accession number 2XJZ) (Fig. 3B) (53)(54)(55) and found that it was in close proximity to LMO2 residues L64 and L71, suggesting a potential hydrophobic interface. L64 and L71 were both highly conserved in LMO2 paralogs, supporting an important functional role for these residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This was surprising since it was not predicted by the structural data on the LMO2/LDB1 interaction. The expression of fulllength recombinant LMO2 and LDB1 in bacteria has been technically challenging, but a fusion protein comprised of full-length LMO2 linked to the LID (i.e., LMO2-LID) was analyzed in solution and crystallized (53)(54)(55)57). Both nuclear magnetic resonance (NMR) and X-ray diffraction structures show binding of the LID in an extended conformation to both LIM domains of LMO2, where backbone contacts predominate between the LID and the NH 2 -terminal part of LMO2, with electrostatic interactions at the COOH terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies suggest that initially synthesized LMO2 protein is intrinsically disordered and that binding to a partner protein confers a configuration that nucleates subsequent protein complex formation. The structure of LMO2:LDB1-LID 36 49 , demonstrates a relatively flat, extended rod structure, able to “present” the LIM fingers to allow for other protein-protein interactions such as with GATA1 50 . By contrast, interaction with VH confers a distinct structure that renders LMO2 inactive due to inefficient binding of natural partners.…”
Section: Discussionmentioning
confidence: 99%
“…First, the use of single domain VH (or indeed scFv) to facilitate co-expression of otherwise intransigent proteins is likely to be a useful general strategy. Molecules like LMO2, that show significant intrinsic flexibility 52 49 , could be stabilized by binding with antibody fragments aided by the masking of hydrophobicity in the interaction with the VH interface.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that LMO2 favored binding to peptides with β-sheet structure and relatively unstable confirmation. Moreover, LMO2 itself also reveals in some degree conformational flexibility that facilitates its interaction with other proteins [ 24 , 25 ]. Thus, it can be speculated that the structure feature of LMO2 itself and its preferred binding peptides benefits mutually to allow it the characteristic of a wide spectrum of protein interactome.…”
Section: Discussionmentioning
confidence: 99%